Effect of beverages, denture cleanser and chlorhexidine gluconate on surface roughness of flexible denture base material: an in vitro study - Sneha Saraf; Sunil Kumar Mishra; Benaiffer Agrawal (European Oral Research)
Purpose: The purpose of the study was to evaluate and compare the effect of beverages, denture cleanser and chlorhexidine gluconate solution on surface roughness of flexible denture base material.Materials and method: Fifty flexible denture base resin specimens measuring 50±1mm in diameter and 0.5±0.05 mm in thickness were fabricated. The specimens were divided into five groups each containing ten specimens. The specimens were immersed in distilled water (Control group A); hot coffee (Group B); cold beverage (Group C); sodium perborate containing denture cleanser (Group D) and 2% chlorhexidine gluconate solution (Group E). The specimens were immersed for 10 min daily in mentioned solutions for up to 60 days. Surface roughness (Ra) was evaluated on the 1st, 20th and 60th day with the help of atomic force microscope. The statistical analysis was done using two-way ANOVA and Tukey’s Post hoc test.Results: The two- way ANOVA revealed that the average Ra values varied significantly depending on the type of solution used for immersion (p<0.001) and the duration of immersion (p<0.001). Variation in surface roughness with cold beverage was highest (p=0.001). On the 60th day the surface roughness of flexible denture base resin material was higher with cold beverage (0.184 μm) and denture cleanser (0.203 μm) than that of distilled water (0.052 μm) hot coffee (0.030 μm) and 2% chlorhexidine gluconate (0.068 μm).Conclusion: Exposure to cold beverage, which was acidic in nature and peroxide containing denture cleanser, produces much rougher surface in the thermoplastic polyamide flexible denture base resin specimens.